PEMBUATAN DAN UJI KEMAMPUAN MEMBRAN KOMPOSIT KITOSAN-PVA UNTUK PEMISAHAN ZAT WARNA RHODAMIN-B - Elvina Rossa, ; Nita Kusumawati, (Matematika dan Sains, 2011)
The aims of research were to know physical characteristic and performance of the chitosan-PVA composite membrane in separating rhodamin-B color with various PVA concentrations and operational pressure. The physical characteristic of membrane tested were tensil strength, stroke, morphology, and porous size. Membrane performance measured were flux value and rejection. Results showed that membrane had high load and high stroke at high concentration of PVA. Load value and stroke value obtained were 0.680-5.646 kgf and 1-9.25%, respectively. Result of SEM analysis showed that membrane produced was microfiltration membrane with porous size of 0.1-1.6 µm. The best flux value was resulted by R-1 membrane at pressure of 5 kg/cm2 namely 27.575 L/m2.hour. While the highest rejection coeficient value was resulted by membrane R-5 at pressure of 1 kg/cm2 namely 91.136%. The rejection coeficient value increased with increasing of PVA concentration, while it decreased with increasing of operational pressure.2 namely 27.575 L/m2.hour. While the highest rejection coeficient value was resulted by membrane R-5 at pressure of 1 kg/cm2 namely 91.136%. The rejection coeficient value increased with increasing of PVA concentration, while it decreased with increasing of operational pressure.